Let it Rain Game linked to iShamba service to provide weekly agri-tips - CGIAR Platform for Big Data in Agriculture (2020)
This was a pilot. Having successfully completed the game and ensured sign up of over 25,000 users across 10 counties, the consortium is now looking to scale the game across all of Kenya. Moreover, iShamba is since provided more localized weather advisory to its users.